MYKIDNEY APPLICATION: OPTIMIZING M-HEALTHCARE FOR ENHANCED CHRONIC KIDNEY DISEASE SELF-CARE MANAGEMENT - A RESEARCH STUDY - BALARAMAN, RAMIYA; SUBBIAH, AHGALYA (Journal of Information Systems and Digital Technologies, 2024)
Chronic Kidney Disease (CKD) poses a significant global health challenge due to deficiencies in patient engagement, leading to disease progression and increased strain on healthcare systems. In chronic kidney disease, insufficient patient engagement in self-management behaviors, such as adhering to dietary restrictions and medications, increases the risk of complications and burdens the healthcare system, underscoring the need for effective strategies to encourage active participation. This project aims to address these challenges by developing the "My-Kidney" mobile health application, designed to empower CKD patients through comprehensive self-management tools and crucial health information. Utilizing an Agile methodology, the development process focuses on iterative feedback and rapid prototyping to ensure user-centric design and functionality. Qualitative research methods are employed to explore patient health management strategies and preferences, informing the application features and usability. By promoting active patient participation in self-care practices and providing tailored support, the "My-Kidney" app aims to improve health outcomes and reduce healthcare burdens. Through technological innovation and patient-centered care, this initiative seeks to catalyze a paradigm shift in CKD management, offering personalized and empowered healthcare delivery for patients worldwide.